Impairing powerhouse in colon cancer cells by hydrazide–hydrazone-based small molecule - Patil, S.; Kuman, M. M.; Palvai, S.; Sengupta, P.; Basu, S. (ACS omega, 2018)
Mitochondrion has emerged as one of the unconventional targets in next-generation cancer therapy. Hence, small molecules targeting mitochondria in cancer cells have immense potential in the next-generation anticancer therapeutics. In this report, we have synthesized a library of hydrazide–hydrazone-based small molecules and identified a novel compound that induces mitochondrial outer membrane permeabilization by inhibiting antiapoptotic B-cell CLL/lymphoma 2 (Bcl-2) family proteins followed by sequestration of proapoptotic cytochrome c. The new small molecule triggered programmed cell death (early and late apoptosis) through cell cycle arrest in the G2/M phase and caspase-9/3 cleavage in HCT-116 colon cancer cells, confirmed by an array of fluorescence confocal microscopy, cell sorting, and immunoblotting analysis. Furthermore, cell viability studies have verified that the small molecule rendered toxicity to a panel of colon cancer cells (HCT-116, DLD-1, and SW-620), keeping healthy L929 fibroblast cells unharmed. The novel small molecule has the potential to form a new understudied class of mitochondria targeting anticancer agent.